Poetics of Value : The Primacy of Insurgency as Marxist Methodology - Mason, Elliot (Historical Materialism Book Series, 2026)
Throughout value-form theory, the present is understood as a homogenising form of subsumption, determining all lives in its commodification of time. In Poetics of Value , Elliot C. Mason employs the 'fugitive' imaginary of black studies to locate other temporalities that antagonise the present. Through close readings of four contemporary poets, Mason finds an exposure to social temporalities that exceed the productive time of value. Poetics of Value proposes the survival of fugitive temporalities as a methodology for Marxism, exceeding the temporal forms of both value and its Marxist criticism.